الظواهر المورفومناخية في المنطقة الشرقية من محافظة ميسان بإستخدام التحسس النائي - السعيدي، علي غليس ناهي; المعارضي، حسين جوبان عريبى; المولى، طارق جمعة علي (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2017)
لقد اعتمد الباحث على البيانات المناخية لمحطتي بستان ودهلران الإيرانيتين، فضلا عن الدراسة الميدانية لرصد المظاهر المورفومناخية وتوثيقها فوتوغرافيا، كما استخدمت مرئية فضائية لمنطقة الدراسة وملفات الارتفاع الرقمي (DEM) وكذلك برامجيات نظام المعلومات الجغرافية الـ (GIS0 وكل ذلك بهدف استكشاف أثر المناخ في العمليات المورفومناخية الجارية في منطقة الدراسة (المنطقة الشرقية في محافظة ميسان) وقد تبين أن للمناخ دور بارز في تلك العمليات (التعرية، التجوية)، ساهم ببروز أشكال مورفومناخية كثيرة أبرزها (الأودية النهرية، الأخاديد، الحزوز، ظهور الحيتان، الكثبان الرملية... إلخ). إن التنوع في الإشكال الأرضية التي كان للمناخ دور في تشكلها يعد عنصر جذب سياحي في منطقة الدراسة.
The researcher has relied on climate data for two Iranian stations, Bustaan and Dahlan, as well as field study to monitor the Morphological-climatic phenomena which are photographic documentation. It also used a satellite vision for the study area and Digital Elevation Files (DEM) as well as Geographic Information System (GIS). All with the aim of exploring impact of climate in current Morphological-climatic processes in the study area (Eastern Province in Maysan Province). It has been found that the climate has a prominent role in these processes such as (erosion, weathering) which contributed to the emergence many Morphological-climatic forms such as the most prominent (river valleys, the canyons, Sand dunes, etc.). That diversity in ground shapes, that climate had a role to play on, considers as a tourist attraction in the study area.
Keywords: الظواهر المورفومناخية -- نظم المعلومات الجغرافية -- الاحوال الجوية -- التحسس النائى -- محافظة ميسان -- العراق